Hemorrhagic Pseudocyst of Pancreas Treated with Coil Embolization of Gastroduodenal Artery: A Case Report and Review of Literature - Sudhir Kumar Jain; Vishnuraja Rajendran; Maneesh K. Jain; Ronal Kori (Case Reports in Surgery)
Hemorrhage into pseudocyst of pancreas can rarely present as life threatening massive UGI bleeding. We present a case of 21-year-old male, admitted to our department, who was a known case of posttraumatic acute pancreatitis and who developed massive upper GI bleeding. CT angiography of abdomen showed aneurysm of gastroduodenal artery. Patient was successfully treated with coil embolization of gastroduodenal artery.